INTERAKSI EDUKATIF PENDIDIKAN ISLAM PERSPEKTIF BUYA HAMKA DALAM MENGHADAPI SOCIETY ERA - Bali, Muhammad Mushfi El Iq; Chairunniza’, Chairunniza’ (Universitas Nurul Jadid, 2020)
This paper aims to examine the unique thinking of Buya Hamka about educational interactions. This is very suitable in fixing the phenomena that occur in the era of society as a material for overcoming conditions of learners and students in maintaining harmony when studying or learning activities. This study uses a qualitative approach to the type of library research (library research). The data source of this study uses primary data and secondary data. Data collection techniques through library research (library research) using descriptive methods. Analysis of the data used in this study are comparative and descriptive methods. The views of Buya Hamka regarding educational interactions include; (a) Learners must be moderate and reflect true examples for students, (b) Learners should have a broad understanding of a science and have a selection of conventional values ​​with contemporary values, (c) Students must know to be well-mannered in associating with students and having an objective attitude in absorbing knowledge, (d) Students must respect the scientific assembly held by the learner. The steps in applying educational interactions in the concept of Buya Hamka Islamic education include; (a) Right intention in pursuing knowledge, (b) Totality and comprehension in pursuing knowledge, (c) Removing laziness and self-distrust, (d) Maintaining civilization and being objective, (e) Maintaining manners in the learning process, and (f) Tolerance in the field of education.